HUBUNGAN PENGETAHUAN DENGAN KESADARAN TERHADAP VAKSIN HUMAN PAPILLOMAVIRUS (HPV) PADA REMAJA PUTRI DI SMP ANGKASA JAKARTA DAN SMP BUDHI WARMAN - Raras Dwinova, (2023)
Background: Human Papillomavirus is a major risk factor for cervical cancer. Cervical cancer can be prevented by administering the HPV vaccine as primary prevention. Vaccines are the most effective way of preventing cervical cancer. Factors of knowledge and awareness about HPV and its vaccine affect the intention to receive the vaccine. This study aims to determine the relationship between knowledge and awareness of the HPV vaccine in female adolescents. Methods: The research design uses descriptive analytic with a cross sectional approach. The analysis test used the Spearman Rank test. The sampling technique used cluster random sampling of 128 respondents. The research instrument uses Knowledge regarding HPV, Cervical Cancer, and HPV vaccine Questionnaire and Awareness about Cervical Cancer, HPV and HPV Vaccines Questionnaire. Results: Test results using the Spearman Rank test stated that there was a relationship between knowledge and awareness of the HPV vaccine in female adolescents with a P value (0.000<0.05). Conclusion: There is a relationship between knowledge and awareness of the HPV vaccine in female adolescents. Suggestion: It is hoped that health workers can provide easy-to-understand education about cervical cancer and the benefits of HPV vaccination, especially for young women. Keywords : Awareness, Human Papillomavirus Vaccine, Middle School Girls